1988
DOI: 10.1080/01496398808060705
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Chlorinated Hydrocarbon Pollutants on Silica Gel

Abstract: A survey of indoor air pollutants was conducted. The removal of six chlorinated hydrocarbons. including methyl chloride, methylene chloride, chloroform. carbon tetrachloride, 1.1.1-trichloroethane, and tetrachloroethylene was performed using adsorption methods. The equilibrium uptakes of the six indoor pollutants on silica gel were determined gravimetrically at 25°C and at pressures up to saturation. The modified potential theory proposed by Dubinin and coworkers was used to correlate the adsorption data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Desiccant materials are a subset of sorbents that are normally used for dehumidification. Previous studies showed that they can also be used to remove gases other than water vapor from air (Hines and Ghosh, 1993; Hines et al., 1993a; Kuo and Hines, 1988 and Popescu and Ghosh, 1999). Kuo and Hines (1988) studied uptake of six chlorinated hydrocarbons (methyl chloride, methylene chloride, chloroform, carbon tetrachloride, 1,1,1‐trichloroethane and tetrachloroethylene) on silica gel and concluded that silica gel can be effectively used to both dehumidify as well as remove pollutants from indoor air.…”
Section: Introductionmentioning
confidence: 99%
“…Desiccant materials are a subset of sorbents that are normally used for dehumidification. Previous studies showed that they can also be used to remove gases other than water vapor from air (Hines and Ghosh, 1993; Hines et al., 1993a; Kuo and Hines, 1988 and Popescu and Ghosh, 1999). Kuo and Hines (1988) studied uptake of six chlorinated hydrocarbons (methyl chloride, methylene chloride, chloroform, carbon tetrachloride, 1,1,1‐trichloroethane and tetrachloroethylene) on silica gel and concluded that silica gel can be effectively used to both dehumidify as well as remove pollutants from indoor air.…”
Section: Introductionmentioning
confidence: 99%
“…The activated carbon AC8‐12 exhibited the highest heat of adsorption of 50.9 kJ mol −1 , while the molecular sieve Mol5A exhibited the lowest heat with 10.0 kJ mol −1 . These values, which are within the ranges reported by earlier researchers, e.g., , are indicative of a physisorption type of interactions between the MeCl and the adsorbent, which in turn, implies easy regeneration of the adsorbents.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a number of isolated studies on the adsorption of MeCl on various adsorbents, such as metal surfaces , , , charcoal , , silica gels , , zeolites , and activated carbon fibers ; see Tab. for a summary of few selected studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [21][22][23] have found that sorption filtration is more effective than other approaches. Desiccant materials are a subset of sorbents that are normally used for dehumidification, and they can also be used to remove gases other than water vapor from air in previous studies [24][25][26][27][28][29]. In the study of Fang et al [28], the air cleaning efficiency of silica gel rotor was evaluated by PTR-MS and sensory assessment, and the results revealed that the measured VOCs were removed effectively by the desiccant wheel with an average efficiency of 94% or higher; more than 80% of the sensory pollution load was removed and the percentage dissatisfied with the air quality decreased from 70% to 20%.…”
Section: Introductionmentioning
confidence: 99%